Implementasi Filsafat Progrevisisme Dalam Pembelajaran Bahasa Indonesia Di Sekolah Dasar ,”Upaya Membangun Kreativitas Dan Kemandirian Siswa”: Progressivism, Indonesian language learning, elementary education, creativity, independence - Supriyanti; Ainur Rofiq; Efa Yulianti; Fatimatuz Zahroh; Nensy Megawati Simanjuntak (LPPM Universitas Madako Tolitoli, 2026)
Education in Indonesia is still dominated by a traditional, teacher-centered, authoritarian approach that provides little space for students to explore and develop their potential. This condition impacts the low creativity and independence of students, particularly in Indonesian language learning in elementary schools. This study aims to examine the application of the philosophy of progressivism as an alternative to building creativity and independence through democratic learning. The method used is qualitative research with a literature study, reviewing literature in the form of books, journals, and relevant articles. The results of the study indicate that progressivism can be implemented through differentiated learning that adapts content, processes, products, and learning environments to students' needs and interests. This strategy encourages active participation, critical thinking, independence, and increases learning motivation. Teachers act as facilitators and motivators, creating a collaborative, contextual atmosphere that aligns with the Independent Curriculum. Overall, progressivism is an innovative solution to improve the quality of Indonesian language learning while developing a creative, independent, and adaptive generation to global challenges.